2009
DOI: 10.1007/s12155-009-9033-2
|View full text |Cite
|
Sign up to set email alerts
|

The Mycorrhizal Fungus, Sebacina vermifera, Enhances Seed Germination and Biomass Production in Switchgrass (Panicum virgatum L)

Abstract: Seed dormancy and slow seedling establishment are two major concerns in switchgrass (Panicum virgatum L.) production, often resulting in a poor stand with reduced productivity. Studies were conducted to investigate the stability of artificial associations between switchgrass and the ectomycorrhizal fungus, Sebacina vermifera, and to evaluate the potential benefits of this novel association in seed germination and biomass production. All six strains of S. vermifera tested had a high frequency of colonization on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 30 publications
5
48
0
Order By: Relevance
“…Nutrient uptake from the soil is not only primarily a function of plant biomass but it is also influenced by plant genotype and environment interactions, especially soil properties, weather, and management practices [27]. One reason that switchgrass was selected as a promising species for biofuel production is that it can be grown on marginal soils, which would minimize competition with food crops for prime arable land [6,25]. Nonetheless, sustainable management of soil nutrients and fertilizers will be important if switchgrass is to become part of a long-term solution to the looming energy crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrient uptake from the soil is not only primarily a function of plant biomass but it is also influenced by plant genotype and environment interactions, especially soil properties, weather, and management practices [27]. One reason that switchgrass was selected as a promising species for biofuel production is that it can be grown on marginal soils, which would minimize competition with food crops for prime arable land [6,25]. Nonetheless, sustainable management of soil nutrients and fertilizers will be important if switchgrass is to become part of a long-term solution to the looming energy crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Switchgrass has higher biomass yield than many annual crops and can be grown on marginal soils, which avoids competition with food crops for prime arable land [1][2][3]. There are two switchgrass ecotype classes, "upland" and "lowland," which refer to latitude.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the newly defined basidiomycete order Sebacinales naturally form a wide spectrum of mycorrhizal types of relationships (31) with the roots of various mono-and dicotyledonous plants (4,11,15,28,30). Two species in particular, Sebacina vermifera [Serendipita vermifera (Oberw.)…”
mentioning
confidence: 99%
“…nov] and its close relative Piriformospora indica, have stimulated considerable attention over the past several years, because they form endophytic and mycorrhiza-like associations with most plant species studied to date (30,32). This is of great interest, because both species are axenically cultivable, possess plant growth-promoting characteristics, and contribute several other benefits to their host plants (4,11,15,28,30). Two previous studies have shown that colonization of roots by P. indica confers drought tolerance in Arabidopsis thaliana and Chinese cabbage (24, 25).…”
mentioning
confidence: 99%